The Relationship of Policy and Supervision with Nurse’s Compliance with The Application of Early Warning Score (EWS) in Inpatients at Tgk Abdullah Syafi'i Hospital - Bashir, Asri; Safrullah, Safrullah (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: The speed and accuracy of a nurse's initial assessment can determine the success of care in emergency patients. Patient emergencies can occur not only outside the Hospital, but also during the patient's hospitalization Objective: The purpose of this study is to determine the relationship between policy and supervision with nurses' compliance with the implementation of the Early Warning Score (EWS) in inpatient patients Method: The design of this study  uses a colleration analytical design with a crossecsional approach, the population in this study is all nurses in the room  The inpatient rawap at RSUD Tgk Abdullah Syafi'I totaled 254 nurses. The sampling technique in this study used a simple technique Random Side of 110 nurses. Result and Discussion: the results of this study show that there is a significant relationship between policy and nurses' compliance with the application of early warning score (EWS) with a p-value of 0.020<0.05. There is a significant relationship between supervision and nurse compliance with the application of the Early Warning Score (EWS) with a p-value of 0.013<0.05. Conclusions: There is a significant relationship between policy and supervision and nurses' adherence to the application of early warning score (EWS) in inpatients